Development of an annotated bibliography for sports sciences via citation analysis of 2012-2016 Bachelor of Sports Science theses - Quebrar, Albert C.; Isip, Jonathan D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2017)
A citation and bibliometric analysis study is performed on the citations of UP Bachelor of Sports Science (BSS) undergraduate theses submitted from January 2012 to July 2016. The aim of the study is to assess the research output and reference usage of BSS researchers. Theses were classified into research subjects while reference citations were gathered for quantitative statistical and citation analysis. Co-citation phenomena between references are also visualized through the use of VOSViewer to supplement contextual and qualitative analysis to the reference literature domain.

Among the principal findings was that BSS thesis have mostly been about sports psychology, applied exercise physiology and sports sociology while research on sports nutrition and sports biomechanics have been uncommon to rare. BSS researchers also relied heavily on journal articles for references. Co-citation cluster maps of authors and journals show that sports science literature are not centralized; reference use is almost exclusively divided between physical sports sciences and sports social sciences.

Through data and findings acquired by the study, an exploratory method of creating a non-critical bibliographic guide to sports science references is undertaken, where entries are evaluated on previous usefulness and relatedness to other previously useful references through quantitative evidence offered by citation frequencies and co-citation frequencies. In addition to regular bibliography information, citation-based annotations are also provided for entries.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Bibliographical citations; Citation analysis